Histoid leprosy: a rare exuberant case - de Andrade, Pedro Jose Secchin (An Bras Dermatol, 2015)
Leprosy is a neglected disease. We point up the need of recognizing the unusual clinical presentations of the disease in order to make early diagnosis and proper treatment possible, and break the transmission chain. The authors report a rare type of multibacillary leprosy: histoid leprosy and present images of numerous well-circumscribed indurated papules and nodules distributed throughout the entire body.